Human anatomy the definitive visual guide - Roberts, Alice (Dorling Kindersley, 2014)
A guide to human anatomy. It features biological wonders of the human body, often at life-size, with spectacular anatomical images showing the body's structure in incredible detail, from bone sutures to lymph nodes. It takes you on a journey through all the body's systems, working down from the head to the toes, with an overview of each system.